DIELECTRIC PROPERTIES OF DENSE COULOMB SYSTEMS - Arkhipov, Yu. V.; Askaruly, A.; Ashikbaeva, A. B.; Davletov, A. E.; Tkachenko, I. M. (Recent Contributions to Physics, 2009)
The possibility to calculate the dynamic local field correction, describing the amendment to the random phase approximation due to the nonideality effects, is demonstrated for one-component plasmas (OCP) in the framework of the moment method without making any additional assumptions. Plasma wave dispersion and decrement are analyzed both numerically and analytically.